2017
DOI: 10.1111/nicc.12333
|View full text |Cite
|
Sign up to set email alerts
|

Development of a modified swallowing screening tool to manage post‐extubation dysphagia

Abstract: Post-extubation dysphagia is a condition that is becoming a growing concern. The condition occurs in 3-62% of extubated patients and can be related to mixed aetiologies, such as neuromuscular impairment, critical illness and laryngeal damage. The risk factors for developing dysphagia in critically ill patients are under-diagnosed and perhaps underestimated. Recent studies recommend the implementation of a standardized swallowing screen to prevent aspiration and decrease pneumonia rate and mortality. The aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 27 publications
0
43
0
1
Order By: Relevance
“…In contrast with post‐stroke patients, there has been little evidence of the evaluation of the screening tools in ICU patients. Because the mechanism for dysphagia can be entirely different in ICU patients, the assessments used for post‐stroke patients might not be applicable, and the development or adaptation of a recognized swallowing screening tool may be needed (Christensen and Trapl, ). In medical ICU patients, only one previous report has described a nurse‐performed screening that was safely conducted with respect to several patient‐centred outcomes (See et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with post‐stroke patients, there has been little evidence of the evaluation of the screening tools in ICU patients. Because the mechanism for dysphagia can be entirely different in ICU patients, the assessments used for post‐stroke patients might not be applicable, and the development or adaptation of a recognized swallowing screening tool may be needed (Christensen and Trapl, ). In medical ICU patients, only one previous report has described a nurse‐performed screening that was safely conducted with respect to several patient‐centred outcomes (See et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…With early screening for dysphagia risks by nurses or SLTs, a preventative approach helps to reduce complications and poorer outcomes. 19,20 Tracheostomy weaning Both swallowing and communication are impacted by the presence of a tracheostomy through redirection of airflow and alterations to valving and pressure systems that power the muscles in normal swallowing. SLTs have specific knowledge and understanding of this physiology and make valuable contributions to MDT decision making regarding tracheostomy manipulation for weaning.…”
Section: Swallowing Impairmentmentioning
confidence: 99%
“…Although dysphagia is common in the cardiac ICU setting, no validated screening tools are available and formal nursing guidelines for bedside dysphagia screening are lacking (Christensen & Trapl, 2017). It is therefore unclear what practices nurses currently use in this setting.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these findings highlight the importance of repeat screening in individuals who fail an initial swallowing screen.Survey results revealed 15 different distinct methods utilised by cardiac surgery ICU nurses for screening swallowing. The noted variability in screening methods may be related to the current lack of ICU practice guidelines and formal training programmes in this area(Christensen & Trapl, 2017). Oral trials of both ice chips and water were the most frequently reported technique, followed by the integration of food and/or liquid trials of increasing viscosity.…”
mentioning
confidence: 99%